2015
DOI: 10.3389/fpsyg.2015.01888
|View full text |Cite
|
Sign up to set email alerts
|

Global Similarities and Multifaceted Differences in the Production of Partner-Specific Referential Pacts by Adults with Autism Spectrum Disorders

Abstract: Over repeated reference conversational partners tend to converge on preferred terms or referential pacts. Autism spectrum disorders (ASD) are characterized by pragmatic difficulties that are best captured by less structured tasks. To this end we tested adults with ASD who did not have language or intellectual impairments, and neurotypical comparison participants in a referential communication task. Participants were directors, describing unlexicalized, complex novel stimuli over repeated rounds of interaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
(81 reference statements)
3
21
0
Order By: Relevance
“…Compared to TD groups that are well‐matched for chronological age, nonverbal IQ and formal language (syntax or vocabulary), ASD groups usually underperform in the production of appropriately informative referring expressions during narrative tasks [Colle, Baron‐Cohen, Wheelwright, & van Der Lely, ; Suh et al, ; Banney, Harper‐Hill, & Arnott, ; Arnold, Bennetto, & Diehl, ]. The same has been found in production studies that have used interactive experimental manipulations of the participant and interlocutor's shared visual perspective [Nadig, Vivanti, & Ozonoff, ; Fukumura, ; Dahlgren & Dahlgren Sandberg, ; Volden, Mulcahy, & Holdgrafer, ; Nadig, Seth, & Sasson, ]. That said, one study that used a very simple narrative elicitation task [Kuijper, Hartman, & Hendriks, ] found no differences between children and adolescents with ASD and TD controls.…”
Section: Introductionmentioning
confidence: 83%
“…Compared to TD groups that are well‐matched for chronological age, nonverbal IQ and formal language (syntax or vocabulary), ASD groups usually underperform in the production of appropriately informative referring expressions during narrative tasks [Colle, Baron‐Cohen, Wheelwright, & van Der Lely, ; Suh et al, ; Banney, Harper‐Hill, & Arnott, ; Arnold, Bennetto, & Diehl, ]. The same has been found in production studies that have used interactive experimental manipulations of the participant and interlocutor's shared visual perspective [Nadig, Vivanti, & Ozonoff, ; Fukumura, ; Dahlgren & Dahlgren Sandberg, ; Volden, Mulcahy, & Holdgrafer, ; Nadig, Seth, & Sasson, ]. That said, one study that used a very simple narrative elicitation task [Kuijper, Hartman, & Hendriks, ] found no differences between children and adolescents with ASD and TD controls.…”
Section: Introductionmentioning
confidence: 83%
“…Yet, individuals with ASD struggled to align the conceptualizations of their communicative signals with those of their interaction partners when the problem space afforded multiple solutions. This impairment could be isolated because the novel communicative setting prevented access to pre-existing contextual cues that cognitively-able individuals with ASD can capitalize on to resolve ambiguity (Au-Yeung, Kaakinen, Liversedge, & Benson, 2015;Birmingham, Stanley, Nair, & Adolphs, 2015;Branigan, Tosi, & Gillespie-Smith, 2016;Brewer, Biotti, Bird, & Cook, 2017;Hahn, Snedeker, & Rabagliati, 2015;Nadig, Seth, & Sasson, 2015;Pijnacker, Hagoort, Buitelaar, Teunisse, & Geurts, 2009) . Under these experimentally-generated conditions, built to recreate the fleeting ambiguities of everyday interaction, communication requires more than pruning a decision tree of possible signals or iteratively optimizing behavioral outcomes (Botvinick & Weinstein, 2014;Donoso, Collins, & Koechlin, 2014;Keysers & Perrett, 2004) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly speakers with autism can successfully complete structured pragmatic tasks (e.g. Nadig et al, 2009;Nadig, Seth, & Sasson, 2015) but continue to demonstrate difficulties in naturalistic contexts. Previous research in conversation analysis has reported that children with autism can use eye gaze for different purposes, subtly meshed with gesture and vocalisation, but do so inconsistently (Dickerson, Rae, Stribling, Dautenhahn, & Werry, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One perspective on the development of pragmatic abilities is based on the notion that very young children's social interactions, especially when supported by competent communicative partners, enable them to acquire social understanding and pragmatic ability through activity, conceptualised variously as 'naïve participation' (Fernyhough, 2008) or 'use before meaning' (Nelson, 1996). Writers in this tradition view the child's access to the social, interpersonal context as primary in development, providing the attuned, collaborative exchanges from which cognition and language are moulded (Trevarthen & Aitken, 2001;Vygotsky, 1978).…”
Section: Conversation As Joint Engagementmentioning
confidence: 99%